2018
DOI: 10.1016/j.neuron.2017.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Localized Myosin II Activity Regulates Assembly and Plasticity of the Axon Initial Segment

Abstract: The axon initial segment (AIS) is the site of action potential generation and a locus of activity-dependent homeostatic plasticity. A multimeric complex of sodium channels, linked via a cytoskeletal scaffold of ankyrin G and beta IV spectrin to submembranous actin rings, mediates these functions. The mechanisms that specify the AIS complex to the proximal axon and underlie its plasticity remain poorly understood. Here we show phosphorylated myosin light chain (pMLC), an activator of contractile myosin II, is h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
121
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(134 citation statements)
references
References 81 publications
13
121
0
Order By: Relevance
“…pMLC was found to have a punctate distribution along the length of the axons ( Figure S10). A recent study had also reported pMLC distribution along the entire length of 3 DIV rat hippocampal axons (38). The latter study and our results also indicate that pMLC is not commonly colocalised with the F-actin patches.…”
Section: Discussionsupporting
confidence: 81%
“…pMLC was found to have a punctate distribution along the length of the axons ( Figure S10). A recent study had also reported pMLC distribution along the entire length of 3 DIV rat hippocampal axons (38). The latter study and our results also indicate that pMLC is not commonly colocalised with the F-actin patches.…”
Section: Discussionsupporting
confidence: 81%
“…We next took advantage of PREM of unroofed neurons to determine the ultrastructural localization of MPS components known to specifically localize along the AIS (Leterrier, 2018). The phosphorylated myosin light-chain (pMLC), an activator of myosin II, was recently reported to associate with the MPS along the initial segment (Berger et al, 2018), together with its partner tropomyosin (Abouelezz et al, 2019b). We found concentrated pMLC at the AIS, with areas showing a ~200 nm periodic pattern on SMLM images ( Fig.…”
Section: Ultrastructural Organization Of Proximal Mps Componentsmentioning
confidence: 95%
“…Rabbit polyclonal anti 480-kDa ankG (residues 2735-2935 of rat 480-kDa ankG, 1:300 for IF, 1:100 for IG) was a gift from Vann Bennett (Duke University, Durham, NC) (Jenkins et al, 2015). Rabbit anti phospho-Myosin Light Chain 2 Thr18/Ser19 (pMLC) was from Cell Signaling Technologies (#3674, 1:50 for IF, 1:20 for IG) (Berger et al, 2018).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
“…Tpm3.1 recruits and activates myosin IIB (Bryce et al, 2003;Gateva et al, 2017), and recent work has revealed an important role for myosin II in AIS structure (Berger et al, 2018;Evans et al, 2017;Wang et al, 2018).…”
Section: Tpm31 Inhibition Leads To the Gradual Collapse Of The Ais Amentioning
confidence: 99%
“…While actin patches are not exclusive to the AIS, AIS actin patches are more stable than patches along the distal axon; the washing away of diffuse molecules by cell permeabilization led to the loss of actin patches in the distal axon, but not in the AIS (Watanabe et al, 2012). In addition, recent work showed that the actin-based non-muscle myosin II is involved in AIS structure and plasticity (Berger et al, 2018;Evans et al, 2017) and associates with axonal F-actin (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%